Mechanical circulatory support devices in left main occlusion: a multicenter study from 2008 to 2020. (3rd October 2022) - Oliveira Campinas, A; Braga, M; Alexandre, A; Costa, R; Dias De Frias, A; Calvao, J; Brandao, M; Passos Silva, M; Pires De Morais, G; Carlos Silva, J; Brochado, B; Luz, A; et al.
Abstract: Introduction: Evidence of benefit in the use of mechanical circulatory support devices (MCS) in patients with acute myocardial infarction (AMI) is scarce. We aimed to evaluate the clinicalcharacteristics, prognosis and factors associated with the use of MCS in patients with AMI due to left main (LM) occlusion. Methods: We performed a retrospective multicenter study of 128 consecutive patients with AMI with ≤12h of presentation with LM occlusion submitted to immediate reperfusion between January 1, 2008, until December 31, 2020 in three terciary hospitals of Portugal. Among this cohort, we divided patients into two groups according to the use of MCS devices. Results: Regarding the baseline characteristics no statistically significant differences were found, except for the presence of cerebrovascular disease (2.9% in group with vs 16.9% in group without MCS, p=0.007) and peripheral artery disease (8.8% in group with vs 22% in group without MCS, p=0.037). We observed that the use of MCS devices was statistically different between the three centers (47.8%, 42%, 8.7%, p<0.001). No differences were found at presentation for ST-segment elevation vs non-ST segment elevation AMI (p=NS). The presence of cardiogenic shock (72.4% vs 45.8%, p=0.002), cardiac arrest (27.5% vs 23.7%, p=0.034) and more severe thrombolysis in myocardial infarction (TIMI) flow at presentation (55.1% vs 35.6%, p=0.015) were more frequent in group with MCS. The rate of 1-year cumulative mortality was high in both groups (31/59=52.5% in the group without vs 47/69=68.1%, p=NS). Also, no statistically significant differences were found in terms of survival, but we observed a trend to higher mortality in those who received MCS as Kaplan-Meier survival curves show (log rank=0.062). Finally, in multivariable analysis, older age [odds ratio (OR), 0.935; 95% CI, 0.87–0.99], the presence of diabetes (OR, 0.223; 95% CI, 0.056–0.88), peripheral artery disease (OR, 0.070; 95% CI, 0.009–0.566) and extra-hospitalar cardiac arrest (OR, 0.06; 95% CI, 0.007–0.543) were characteristics associated with lower odds of receiving MCS. Contrarily, male sex (OR, 5; 95% CI, 1–20.4) and the presence of cardiogenic shock (OR, 5.7; 95% CI, 1.42–23) were factors associated with higher use of MCS. Conclusion: The use of MCS does not seem to modify prognosis in patients admitted withAMI due to left main occlusion. Only cardiogenic shock and male gender were predictors of MCS use. Funding Acknowledgement: Type of funding sources: None.